Sequential C-reactive protein: a cheap and a valuable biomarker in patients with sepsis - Dhakad, Vinod; Trikha, Sushma; Singh, Neelima; Kansal, Archana (International Journal of Research in Medical Sciences, 2019)
Background: C-reactive protein (CRP) is a valuable biomarker of sepsis. Levels of CRP increase very rapidly in response to infection, and decrease just as rapidly with the resolution of the condition. The aim of the research was to study, C-reactive protein levels in patients of sepsis and to study the pattern of CRP levels in patients of Sepsis with hypertension, diabetes, smokers and alcoholics. Methods: This prospective observational cohort study was conducted from December 2016 to September 2018 in 100 cases of sepsis. Patients presenting in emergency with sepsis were included as subjects. C- reactive protein was measured in every patient at the time of admission and after 72 hours. Facts related to history, clinical examination and biochemical parameters were recorded in a pretyped proforma. Data were analyzed using SPSS software. Results: Males outnumbered females. Most of the patients40(40%) were in the age group of less than 30 years age group. CRP levels were markedly elevated in patients with diabetes mellitus (92.2±102.63) as compared to patients with hypertension (36.66±26.97) or both (24.20±12.87). CRP levels were higher in alcoholics (60.59±44.20) as compared to smokers (13.37±10.96). CRP levels decreased significantly after 72 hours compared to CRP levels at the time of admission (p <0.001) across all patients suggestive of acute infection. Conclusions: Serial CRP measurement, rather than a single determination at the time of admission, is cheap and valuable in the diagnosis of sepsis and in monitoring the response to therapy. CRP levels shows exaggerated response in diabetes mellitus and alcoholics with sepsis in this study.